Influence of shallow core-level hybridization on the electronic structure of post-transition-metal oxides studied using soft X-ray emission and absorption - McGuinness, C; Stagarescu, C; Ryan, P; Downes, J; Fu, D; Smith, K; Egdell, R (American Physical Society, 2003)
The influence of shallow core-level hybridization on the electronic structure of the post-transition metal oxides ZnO, CdO, In2O3, and SnO2 has been investigated using high-resolution soft x-ray emission and absorption spectroscopies. Synchrotron radiation excited OKα emission spectra provide a direct measure of the O 2p partial density of states and shallow core-level hybridization for this series of transparent conducting materials and reveal significant mixing of O 2p and shallow-core metal d states for ZnO, CdO and In2O3. The experimental data are compared with local density approximation and tight-binding band structure calculations and with previous experimental determinations of direct and indirect band gaps. Rocksalt CdO, bixbyite In2O3, and rutile SnO2 all adopt structures with metal cations in sites with locally centrosymmetric coordination. This prevents hybridization of O 2p states with metal 4d states at the zone center, but mixing away from Γ leads to indirect band gaps for CdO and In2O3. A revised value for the lowest indirect band gap in CdO is proposed and the overall trends in the band gap are discussed in terms of the separation between O 2p and metal 4d states. The experimental investigation has been extended to study the effects of Sn doping in In2O3.